2021
DOI: 10.2196/18410
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Together for People With Multiple Sclerosis and Their Care Partners: Protocol for a Feasibility Randomized Controlled Trial of a Dyadic Intervention

Abstract: Background Physical activity (PA) is beneficial for all people; however, people affected by multiple sclerosis (MS) find regular PA challenging. These people may include individuals with advanced disabilities and their care partners. Objective The objective of this study is to determine the feasibility of a dyadic PA intervention for people with advanced MS and their care partners. Methods This study is a ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Care partners (CP) of PwPD experience tremendous burden due to their role as caregivers, and recent reviews have identified negative changes in physical health, depression, and even increased risk of all-cause mortality [8,9]. Dyadic exercise interventions engaging both care recipients and CP have been identified as a means to reduce CP burden and improve wellbeing across other neurodegenerative diseases [10][11][12]. However, no such interventions have been conducted for PwPD and their CP.…”
Section: Introductionmentioning
confidence: 99%
“…Care partners (CP) of PwPD experience tremendous burden due to their role as caregivers, and recent reviews have identified negative changes in physical health, depression, and even increased risk of all-cause mortality [8,9]. Dyadic exercise interventions engaging both care recipients and CP have been identified as a means to reduce CP burden and improve wellbeing across other neurodegenerative diseases [10][11][12]. However, no such interventions have been conducted for PwPD and their CP.…”
Section: Introductionmentioning
confidence: 99%
“…The full details of the PAT-MS intervention content, including theoretical frameworks, are reported in the published protocol. 10 In brief, the content and processes of PAT-MS are theoretically grounded in the Theory of Dyadic Illness Management (TDIM), 11 with direction from social cognitive theory (SCT) 12 and selfdetermination theory (SDT). 13 The basic tenet of TDIM is that the way that dyads affected by chronic diseases (eg, MS) appraise disease impact as an interdependent team influences how they engage in health-promoting behaviors (eg, PA), which, in turn, influences dyadic health.…”
mentioning
confidence: 99%
“…11 The TDIM emphasizes the importance of targeting both partners simultaneously to ensure sustainable change in health outcomes for each individual and for the dyad. We used SCT 12 and SDT 13 to identify key theoretical constructs (eg, self-efficacy from SCT; relatedness and intrinsic motivation from SDT) that influence PA behavior to be included in PAT-MS. Also, SCT 12 and SDT 13 provided guidance for selecting behavior change techniques (eg, goal setting, problem-solving, and behavioral practice) 14 to alter or redirect causal processes that regulate PA behavior (see Table 1 in the published protocol 10 for details of behavior change techniques in PAT-MS). PAT-MS includes 3 main components: (1) education (ie, provision of information about PA, shared disease appraisal, and benefits of shared participation in PA as a dyadic coping strategy); (2) guidance from a trained activity coach (ie, an activity coach will provide verbal and written instruction, including behavioral strategies commonly used in dyadic health interventions for persons with neurologic conditions and their care partners 15 ); and (3) social support (ie, provision of practical, emotional, and informational support, including links to community resources for continued PA participation and opportunities to learn from other group members).…”
mentioning
confidence: 99%